Electrophysiological studies of malaria parasite-infected erythrocytes: Current status - Staines, Henry M. (2007)
The altered permeability characteristics of erythrocytes infected with malaria parasites have been a source of interest for over 30 years. Recent electrophysiological studies have provided strong evidence that these changes reflect transmembrane transport through ion channels in the host erythrocyte plasma membrane. However, conflicting results and differing interpretations of the data have led to confusion in this field. In an effort to unravel these issues, the groups involved recently came together for a week of discussion and experimentation. In this article, the various models for altered transport are reviewed, together with the areas of consensus in the field and those that require a better understanding.